Performance in kimono grip strength tests among Brazilian Jiu-Jitsu practitioners from different levels - Correa da Silva, B. V.; Marocolo Junior, M.; de Moura Simim, M. A.; Franchini, E.; Ribeiro da Mota, G. (Journal of Combat Sports and Martial Arts, 2014)
Introduction. In combat sports involving grappling, muscular strength is considered one of the most important physical components to be developed, specifically in upper limbs. The objective of our study was to examine if there are differences between elite and non-elite Brazilian Jiu-Jitsu practitioners, in two kimono grip strength endurance tests. Material and methods. Forty Brazilian Jiu-Jitsu practitioners were divided in four groups: Advanced; Non-Advanced; Recreational and Beginners. All participants performed the kimono grip pull-up tests, both maximum static lift and maximum number of repetitions, until maximal volunteer fatigue with appropriated interval. A One Way analysis of variance was used to compare the groups. Tukey test was used as post hoc test. Results. There were no difference in maximum static lift and maximum number of repetitions tests between Advanced (18 ± 3 rep; 62 ± 14 s) and Non-Advanced (17 ± 3 rep; 60 ± 0 s). There was difference (p<0.05) in maximum static lift test between Recreational (43 ± 5 s) and Beginners (28 ± 9), but not in maximum number of repetitions test between Recreational (9 ± 3 rep) and Beginners (7 ± 3) respectively. Moreover, we observed differences (p>0.05) between both tests in the Recreational and Beginners groups compared with Advanced and Non-Advanced groups. Conclusions. We conclude that isometric kimono grip pull-up test is able to discriminate isometric strength endurance between 4 different levels of Brazilian Jiu-Jitsu players groups, but dynamic kimono grip pull-up test only discriminate strength endurance with larger differences concerning practice levels.